Enhancement of Subgrade Properties Using Magnesium Oxide for Pavement Construction - A. Salem, Lubna; Hasan Taher, Amer; Mancy Mosa, Ahmed (International Journal of Engineering and Technology, 2018)
This study aims to use Magnesium Oxide (MgO) as one of the modern additives to improve the properties of subgrade and consequently improve the pavements system structure and durability as well as reducing the cost of construction and maintenance of the constructed pavements. The study adopted California Bearing Ratio (CBR) testing method and cyclic triaxial compression test (this test is used to determine the soil resilient modulus (Mr)) to investigate the influence of MgO on the properties of a selected soil obtained from Baghdad city. Six doses (0.25%, 0.5%, 0.75%, 1%, 1.25%, and 1.5% of the dry weight of soil) of MgO were added to the selected soil to attain the objective of this study. The results exhibited that CBR values increased from 3.39% to (13.59%, 18.45%, 27.54%, 25.24%, 16.99%, and 14.56%) respectively, the Mr values increased from 35 MPa to (83, 97,150, 137, 110 and 103 MPa) respectively and the swelling ratios decreased from 3.4% to (1.51%, 0.80%, 0.61%, 0.66%, 1.18%, and 1.97%) respectively by adding MgO doses, previously, mentioned. Based on these results the optimum MgO dose is (0.75% by the dry weight of soil) as it satisfies the highest CBR and Mr values and the lowest swelling ratio. Â Â Â